Registered Nurses’ Characteristics and Their Levels of Compassion Competence and Satisfaction: A Cross-Sectional Survey - Jacqueline Galica; Stephanie Saunders; Chiamaka Madu; Ziwei Pan; Hok Kan Ling; Jennifer Waite; Denise Neumann-Fuhr; Erna Snelgrove-Clarke (SAGE Open Nursing)
Introduction Although registered nurses are expected to treat patients with care and compassion, a variety of characteristics may influence their ability to express compassion. Objectives (1) To assess registered nurses’ level of compassion competence and compassion satisfaction, and; (2) to explore how individual-level, employment-related, and organization-level characteristics are associated with their level of compassion competence and compassion satisfaction. Methods Registered nurses working in any practice setting in Ontario, Canada, completed a cross-sectional electronic survey of valid and reliable measures. Descriptive statistics and multiple linear regression analyses were used to address study objectives. Results One hundred eighty-one registered nurses participated. Most identified as female ( n  = 157; 96.3%), Caucasian ( n  = 144; 88.3%), and completed baccalaureate training as their highest level of education ( n  = 80; 50.6%). Participants’ average compassion competence score was higher than average (4.18 on a 5-point scale), and most participants ( n  = 171, 98.3%) reported moderate to high levels of compassion satisfaction. Compassion satisfaction was the only significant predictor of compassion competence, which indicated a positive relationship ( β = 0.344, p  < .001). Compassion competence was among a variety of significantly positive predictors of compassion satisfaction ( β = 0.652, p  < .001). The other positive significant predictors of compassion satisfaction were higher than baccalaureate education ( β = 0.363, p  < .001), full-time work status ( β = 0.253, p  = .012), working in organizations with greater compassion practices ( β = 0.114, p  = .005), and organizations with higher climate for change ( β = 0.292, p  < .001). Conclusions Study findings illuminate varying degrees of significance for individual-level, employment-related, and organization-level characteristics and how these predict registered nurses’ levels of compassion. These distinctions have important implications for intervention development and future research in understanding compassionate care among nurses.